Ploidy studies in adenomatous polyps of the colon. - Whitehead, F (1985)
The nuclei of colonic adenomatous polyps and some colonic carcinomas have a normal diploid profile. The remaining carcinomas are aneuploid, and this change most probably occurs after the dysplasia that determines invasiveness, because even adenomatous polyps with carcinoma in situ are diploid.